E-Leadership and Teleworking in Times of COVID-19 and Beyond: What We Know and Where Do We Go - Contreras, Francoise; Baykal, Elif; Abid, Ghulam (Frontiers in Psychology, 2020)
Suddenly, COVID-19 has changed the world and the way people work. Companies had to accelerate something they knew was imminent in the future, but not immediate and extremely humongous. This situation poses a huge challenge for companies to survive and thrive in this complex business environment and for employees, who must adapt to this new way of working. An effective e-leadership, which promotes companies’ adaptability, is needed. This study investigates the existing knowledge on teleworking and e-leadership; and analyzes the supposed challenges. The literature review shows that companies with effective e-leadership can view teleworking as an opportunity. It is advantageous for not only companies’ productivity but also the environment and people who work remotely. However, traditional or no leadership can result in some risks. Thriving in remote work environments implies that managers must adjust the companies’ structure, making them less hierarchical, and developing new abilities to establish a strong and trustworthy relationship with their employees to maintain their competitiveness, while retaining a genuine concern for their employees’ well-being. Similarly, successful e-leadership must be able to consolidate and lead effective virtual teams to accomplish organizational goals. This study contributes to the literature and leaders during the pandemic.